Hubungan Antara Perilaku Ibu Tentang PemberianMakanan Pendamping Asi (Mp-Asi) Dengan PerkembanganMotorik Halus Pada Bayi Di Kelurahan Bulakan KabupatenSukoharjo - Mitayani, Nadya; , Ir Listyani Hidayati, M. Kes (2016)
Introduction: Development is the increasing ability of the structure, its functions, including the development of emotional, intellectual, and behaviors as a result of interaction with environment. Children under age five are categorited as golden period of growth and development. Children development is extremely influenced by parenting and stimulus that is given to children. Parenting in feeding consisted of breastfeeding practices and the provision of complementary feeding. Objective: This research aimed to determine the relationship between mothers' behavior of the provision of complementary feeding and the fine motor skills' development on infants aged 6-24 months in Bulakan, Sukoharjo. Method of research: Type of research was observation study with crosssectional approach. The sample used was Infants aged 6-24 months who attended at posyandu Bulakan, Sukoharjo. Sampling method was accidental sampling technique, and statistical test using Chi-square correlation test. Mothers' behavior was obtained by questionnaire and fine motor skills' development is obtained by direct observation to the respondents. Results: The results showed that mothers with good behavior of complementary feeding and have toodlers with good fine motor skills' development was 32%. Responden with low score of complementary feeding behavior and have toodlers with lack of fine motor skills' development was 44%. The relationship between the two variables were shown from Chi Square test with p = 0.000. Conclusion: There was a relationship between behaviour of each mothers about giving solid food with fine motoric development in aged 6-24 month at Bulakan village Sukoharjo district.